2015
DOI: 10.1073/pnas.1417197112
|View full text |Cite
|
Sign up to set email alerts
|

l -cysteine reversibly inhibits glucose-induced biphasic insulin secretion and ATP production by inactivating PKM2

Abstract: Increase in the concentration of plasma L-cysteine is closely associated with defective insulin secretion from pancreatic β-cells, which results in type 2 diabetes (T2D). In this study, we investigated the effects of prolonged L-cysteine treatment on glucosestimulated insulin secretion (GSIS) from mouse insulinoma 6 (MIN6) cells and from mouse pancreatic islets, and found that the treatment reversibly inhibited glucose-induced ATP production and resulting GSIS without affecting proinsulin and insulin synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 59 publications
1
50
0
Order By: Relevance
“…In contrast, we notice in some other papers that the levels of plasma total cysteine correlates positively with the obesity or fat mass of patients [15-17]. A recent study suggested that the increased concentration of L-cysteine can inhibit insulin secretion from pancreatic β-cells through binding and inactivation of pyruvate kinase muscle isoform 2 [18]. With these conflicting reports, we intend to explore the effects of NAC on AGEs generation and diabetic wound healing.…”
Section: Introductionmentioning
confidence: 88%
“…In contrast, we notice in some other papers that the levels of plasma total cysteine correlates positively with the obesity or fat mass of patients [15-17]. A recent study suggested that the increased concentration of L-cysteine can inhibit insulin secretion from pancreatic β-cells through binding and inactivation of pyruvate kinase muscle isoform 2 [18]. With these conflicting reports, we intend to explore the effects of NAC on AGEs generation and diabetic wound healing.…”
Section: Introductionmentioning
confidence: 88%
“…Briefly, Min6 cells were seeded into a 96-well plate overnight and treated with concentrations (0 μmol/l, 10 μmol/l, 20 μmol/l, 30 μmol/l, 40 μmol/l, and 50 μmol/l) of DMDD. After incubation for 24 h, cell survival was measured by using a CCK8 as described previously [18].…”
Section: Plant Materials and Extraction And Isolation Of Dmddmentioning
confidence: 99%
“…This includes the anionic dye Coomassie G-250 (referred to as Blue Native or BN; Schägger and von Jagow, 1991;Krause and Seelert, 2008;Luo et al, 2017). Recently, significant improvements in resolution have been made through use of low (<0.1%) concentrations of the anionic detergent SDS (Nowakowski, 2014;Nakatsu, 2015) or LDS (Arnold et al, 2014) as well as milder negatively charged detergents such as deoxycholate (DOC) with a variation on the Clear Native (CN) approach (Wittig et al, 2007). It should also be noted that the anionic detergent is typically left out of the sample buffer and samples are separated at temperatures from 4°to 7°C to maintain the native forms of the protein and complexes.…”
Section: Background Informationmentioning
confidence: 99%